Detection of NEO in muskmelon fruits inoculated with Fusarium sulphureum and its control by postharvest ozone treatment. (15th July 2018) - Hua-Li, Xue; Yang, Bi; Raza, Hussain; Hu-jun, Wang; Lu-Mei, Pu; Mi-Na, Nan; Xiao-Yan, Cheng; Yi, Wang; Yong-Cai, Li
Highlights: A method of UPLC-MS/MS was developed for NEO analysis in Fusarium rot of muskmelon fruits. Ozone effectively reduced the lesion expansion and NEO accumulation in Fusarium rot of muskmelon. Ozone was involved in degradation of NEO. Abstract: Fusarium rot of muskmelon, caused by Fusarium spp., is one of the most important postharvest decays, that not only causes economic losses but leads to trichothecenes contamination. A rapid and sensitive method was developed for neosolaniol (NEO) analysis in muskmelon inoculated with F. sulphureum, utilizing acetonitrile/water (84:16, v/v) extraction and PriboFast M270 columns purification and UPLC-MS/MS detection. Method validation was evaluated by linearity (R ≥ 0.9990), recovery (88.1–136.9%), precision (RSD ≤ 3.97%) and sensitivity (LOD, 0.5 μg/kg; LOQ, 1.5 μg/kg). The effect of ozone treatment on Fusarium rot development and NEO accumulation in inoculated muskmelon was also evaluated. The results showed that UPLC-MS/MS method was suitable for analyzing NEO in inoculated muskmelon, and 1.10 mg/l ozone treatment for 120 min significantly controlled Fusarium rot development and NEO accumulation in fruits after 5, 8 and 11 days. In vivo tests showed that ozone at 1.10 mg/l effectively degraded NEO in acetonitrile.